Faulting and Folding of the Transgressive Surface Offshore Ventura Records Deformational Events in the Holocene - Perea, Hector; Ucarkus, Gülsen; Driscoll, Neal; Kent, Graham; Levy, Yuval; Rockwell, Thomas (Frontiers in Earth Science, 2021)
Identifying the offshore thrust faults of the Western Transverse Ranges that could produce large earthquakes and seafloor uplift is essential to assess potential geohazards for the region. The Western Transverse Ranges in southern California are an E-W trending fold-and-thrust system that extends offshore west of Ventura. Using a high-resolution seismic CHIRP dataset, we have identified the Last Glacial Transgressive Surface (LGTS) and two Holocene seismostratigraphic units. Deformation of the LGTS, together with onlapping packages that exhibit divergence and rotation across the active structures, provide evidence for 3 to 4 deformational events with vertical uplifts ranging from 1 to 10 m. Based on the depth of the LGTS and the Holocene sediment thickness, age estimates for the deformational events reveal a good correlation with the onshore paleoseismological results for the Ventura-Pitas Point fault and the Ventura-Avenue anticline. The observed deformation along the offshore segments of the Ventura-Pitas Point fault and Ventura-Avenue anticline trend diminishes toward the west. Farther north, the deformation along the offshore Red Mountain anticline also diminishes to the west with the shortening stepping north onto the Mesa-Rincon Creek fault system. These observations suggest that offshore deformation along the fault-fold structures moving westward is systematically stepping to the north toward the hinterland. The decrease in the amount of deformation along the frontal structures towards the west corresponds to an increase in deformation along the hinterland fold systems, which could result from a connection of the fault strands at depth. A connection at depth of the northward dipping thrusts to a regional master detachment may explain the apparent jump of the deformation moving west, from the Ventura-Pitas Point fault and the Ventura-Avenue anticline to the Red Mountain anticline, and then, from the Red Mountain anticline to the Mesa-Rincon Creek fold system. Finally, considering the maximum vertical uplift estimated for events on these structures (max ~10m), along with the potential of a common master detachment that may rupture in concert, this system could generate a large magnitude earthquake (>Mw 7.0) and a consequent tsunami.